The effect of project-based learning model on students’ IPAS learning creativity - Khlisnida Siswandari; Sumadi Sumadi; Hairida Hairida; Agung Hartoyo; Ricka Tesi Muskania (Universitas Sebelas Maret, 2025)
This study aims to determine the effect of the project-based learning model (PjBL) on the learning creativity of fifth-grade science students in elementary school. This study uses a quantitative approach with a quasi-experimental design method and nonequivalent control group design. The research sample consisted of 46 fifth-grade students of SD Negeri 18 Pontianak Timur, divided into an experimental class (23 students) and a control class (23 students). The data collection technique was carried out using tests with pre-test and post-test instruments. Data were analyzed using descriptive statistics and independent t-tests after fulfilling the prerequisite tests for normality and homogeneity. The results showed a significant difference between the experimental and control groups with a p value <0.05. The average posttest of the experimental group (82.61) was higher than the control group (55.24). Analysis per indicator showed that the experimental group excelled in all aspects of fluency (68.50% vs. 64.12%), flexibility (81.52% vs. 38.59%), originality (89.14% vs. 52.72%), and elaboration (89.12% vs. 85.87%). This study proves that the PjBL model has a positive and significant effect on the creativity of fifth-grade students in learning science, so it can be used as an innovative learning alternative to support the development of 21st-century skills in the context of the Independent Curriculum.